THE RATIONAL APPROACH TO THE PROVED THERAPY OF АТОPIC DERMATITIS - Кaliuzhna, L.D.; Shmiglo, M.М.; Ibragim, U.Т.; Uvarenko, Е.А. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Atopic dermatitis represents as the multifactor  generically determined disease of a skin. They determined a general level IgE and allergen specific IgE-antibody to an acaruses of a home dust, investigated association of atopic dermatitis with fungal infection of a skin and its appendages, determined a status of lipid peroxidation in the patients with atopic dermatitis.